Coherent backscattering (CBS) for biosensing application - Muhammad Rasyidil Bin Zulkifli (Nanyang Technological University, 2023)
Coherent Backscattering (CBS) is an optical phenomenon that has attracted scientific attention in the recent years due to its potential application in various medical and technological domains. The phenomenon of CBS occurs when light undergoes scattering in an optically random media such as biological tissues. The backscattered photons result in the formation of a cone like intensity pattern in the backward direction and is known as the CBS cone. CBS can provide valuable insights and understanding into the microscopic structure and properties of the medium through which the light has travelled. In this study, the research is focused on investigating the usefulness of CBS and the potential relationship between varying degrees of surface roughness (Ra) and the transport mean free path values ( ) in the biological tissues. Initial investigations were carried out on phantom tissues to explore the relationship between surface roughness and light transport, which uncovered a potential finding that support the inverse relationship between the and the scattering event on human skin. It was found that higher surface roughness led to more scattering events, resulting in a shorter value and a wider CBS cone. Building on this knowledge, the experiment was extended to actual human skin. It was observed and confirmed the same inverse relationship between the surface roughness of human skin and the values. Despite the inherent complexity of human skin, similarities were observed between phantom tissues and actual human skin. This studies sheds light on the potential for further research into the structure of human skin. This exploration of CBS could open new avenues of study and non-invasive medical diagnostic techniques.